ANALISIS KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL TIPE HIGHER ORDER THINKING SKILLS (HOTS) DITINJAU DARI TAHAPAN PEMECAHAN MASALAH POLYA - Riya Dwi Puspa; Abdur Rahman Asari; Sukoriyanto Sukoriyanto (FMIPA UNIVERSITAS NEGERI MALANG, 2019)
High Order Thinking Skil (HOTS) type questions have been applied to National Exams so the efforts to improve students’ thinking skills at a higher level are continued. This research is a qualitative research which aims to describe the ability of students to solve HOTS type problems in term of the stages of Polya solving. Thus research was conducted in SMK Telkom Malang in the odd semester of 2019/2020 school year. The reasearch subjects in this article were 12th grade students on statistical material. The results of this study indicate that high ability students are able to complete all stages of problem solving polya, capable students are able to understand problems, but are less able to make plans, do the plans and look at the results. The low ability students are less able to do all of the stages in problem solving polya well.